O diretor, o professor e o educador: “O peso do mundo nas coisas” no teatro de claudio longhi, novo diretor do “piccolo” de milão (Olhares, 2020)
Claudio Longhi has been appointed Artistic Director of the “Piccolo Teatro di Milano”. This article reflects on a recent conversation with Claudio Longhi on the future of the famous Italian theater, on its new direction as well as on Longhi’s lastest performance as artistic director of ERT (Emilia Romagna Teatro): Il Peso del mondo nelle cose (The Weight of the World in Things) by Alejandro Tantanian.
Keywords: Artistic direction; Theatrical direction; Theatre Ante-Covid Times; Theatre Post-Covid Times